A 39-Years-Old Female with Left Anterior Epistaxis: Case Report - Anggraini, Irene Oktavia; Gumelar, Halim; Adji, Iwan Setiawan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this report is to present a case of a left anterior epistaxis in a 39-years-old female, analyze its etiology, risk factors, clinical symptoms, diagnostic examinations, and the treatment provided. This report also highlights the importance of prevention and proper management to improve patient prognosis. Methodology: The methodology used in this report is a clinical case study. Data were collected through anamnesis, physical examination, and supporting examinations such as CT scan and histopathology. The patient's management was analyzed based on existing medical theories and appropriate treatment was provided according to the patient's condition. Results: The patient was diagnosed with a left maxillary abscess, presenting with persistent pain and swelling in the left cheek for two months. CT scan findings suggested left-sided sinusitis with a possible abscess, while histopathology confirmed chronic sinusitis.The patient received antibiotic therapy (Ceftriaxone and Metronidazole), symptomatic treatment (Santagesic, Methylprednisolone, and Ranitidine), and education on oral hygiene and follow-up care.The patient had a history of left maxillary surgery and smoking habits, both of which were identified as significant risk factors for developing the condition. Applications/Originality/Value: This report provides insights into the importance of early diagnosis and proper management in maxillary abscess cases.The findings can be useful for healthcare professionals to understand clinical signs and effective treatment approaches for similar cases.The study emphasizes the need for preventive measures, such as maintaining good oral hygiene and avoiding risk factors like smoking.